2014
DOI: 10.1096/fj.14-253831
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage polarization phenotype regulates adiponectin receptor expression and adiponectin anti‐inflammatory response

Abstract: Adiponectin (APN), a pleiotropic adipokine that exerts anti-inflammatory, antidiabetic, and antiatherogenic effects through its receptors (AdipoRs), AdipoR1 and AdipoR2, is an important therapeutic target. Factors regulating AdipoR expression in monocyte/ macrophages are poorly understood, and the significance of polarized macrophage activation in controlling AdipoR expression and the APN-mediated inflammatory response has not been investigated. The aim of this study was to investigate whether the macrophage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 64 publications
5
77
0
1
Order By: Relevance
“…In humans, adiponectin induced M2 polarization and attenuated the expression of M1 markers by ATMs and stromal-vascular cells of adipose tissue [75]. Recently, it has been reported that macrophage polarization is crucial for the regulation of adiponectin receptor expression and differential adiponectin-mediated macrophage inflammatory responses [76]. Adiponectin reduces lipolysis in murine adipocytes [77].…”
Section: Adipose Tissue Inflammationmentioning
confidence: 99%
“…In humans, adiponectin induced M2 polarization and attenuated the expression of M1 markers by ATMs and stromal-vascular cells of adipose tissue [75]. Recently, it has been reported that macrophage polarization is crucial for the regulation of adiponectin receptor expression and differential adiponectin-mediated macrophage inflammatory responses [76]. Adiponectin reduces lipolysis in murine adipocytes [77].…”
Section: Adipose Tissue Inflammationmentioning
confidence: 99%
“…Adiponectin-mediated alternatively activated macrophage polarization was partially dependent upon the adiponectin-heme oxygenase 1 axis. Finally, macrophage polarization differentially affects adiponectin receptor expression [66]. Classically activated macrophages, stimulated by IFN-γ-LPS, decreased expression of adiponectin receptors, while anti-inflammatory cytokines IL-4 and IL-10 stimulated adiponectin receptor expression in peritoneal and bone marrow-derived macrophages.…”
Section: Adipokinesmentioning
confidence: 99%
“…Adiponectin reduces the secretion and the activity of TNF and IL-6, and induces the production of anti-inflammatory mediators, such as IRAK-1 (IL-10 and IL-1 receptor antagonist), in macrophages, monocytes, and dendritic cells. Adiponectin also enhances the number of T reg cells [13,14] . This cytokine is a key link between obesity and autoimmunity: despite being secreted by the adipose tissue, its levels are decreased in the serum of overweight patients and increased with calorie restriction [15][16][17] .…”
mentioning
confidence: 99%